2019
DOI: 10.1088/1361-6528/ab19c9
|View full text |Cite
|
Sign up to set email alerts
|

Tin oxide artificial synapses for low power temporal information processing

Abstract: Lateral memristors configured with inert Pt contacts and mixed phase tin oxide layers have exhibited immediate, forming-free, low-power bidirectional resistance switching. Activity dependent conductance and relaxation in the low resistance state resembled short term potentiation in biological synapses. After scanning probe microscopy, x-ray photoelectron spectroscopy and electrical measurements, the device characteristics were attributed to Joule heating induced decomposition of the minority SnO phase and form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…[10] Tin oxide is a low-cost semiconducting material with proven applications including high performance transparent field effect transistors [11,12] , gas sensors [13] and, recently, resistive switching devices. [14][15][16] In addition to non-volatile resistive switching which has been attributed to electromigration of oxygen vacancies [14] , the conductivity of SnO x can also be widely modulated by Joule heating. This is due to the well-known temperature-driven disproportionation reaction [17] ,…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Tin oxide is a low-cost semiconducting material with proven applications including high performance transparent field effect transistors [11,12] , gas sensors [13] and, recently, resistive switching devices. [14][15][16] In addition to non-volatile resistive switching which has been attributed to electromigration of oxygen vacancies [14] , the conductivity of SnO x can also be widely modulated by Joule heating. This is due to the well-known temperature-driven disproportionation reaction [17] ,…”
Section: Introductionmentioning
confidence: 99%
“…Sn-centres produced after this reaction are n-type dopants in SnO 2 and cause significantly increased electrical conductivity. This mechanism has been exploited in nanoscale resistive switching devices formed on SnO x with high-and low-resistance states separated by more than three orders of magnitude [16] . The low-resistance states (LRS) in these devices were volatile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decomposition of SnO impurities at similar annealing temperatures has also been observed previously. [33] It is worth noting that films of good optical quality can still be obtained at temperatures below 400 °C, however at least ≈300 °C was required to obtain dense and structurally robust coatings. In fact, at lower temperatures the precursors do not fully decompose, and flaky salt residues are observed on the coating surface.…”
Section: Effect Of Deposition Temperaturementioning
confidence: 99%
“…In particular, metal oxide-based materials such as AlO x , NiO x , TiO x and HfO x are currently extensively discussed because of the simplicity of the material [10,12,13,14]. Among these materials, AlO x has been widely applied in gate insulator layers [15,16,17,18] and has attracted extensive attention in the RRAM field owing to its wide band gap (~8.9 eV), high thermal stability with Si and Pt, high dielectric constant (~8) and large breakdown electric field [10,14,19,20,21,22] as Kim et al has reported [19,20,23,24,25,26]. In addition, the superior elasticity [27] and high toughness [28] make it possible for AlO x to be applied under various conditions including vibration and pressure environments [29,30,31].…”
Section: Introductionmentioning
confidence: 99%